Role of External Control in Reducing Financial Corruption - Abdulrasool Abdul Abbas Sahib; Mohammed Salman Dawood (International Forum of Researchers and Lecturers, 2025)
This study aimed to explore the role of external oversight in reducing the phenomenon of financial corruption. To achieve this, a sample of administrators, accountants, and auditors from Al-Furat Al-Awsat Technical University were surveyed, with 60 questionnaires distributed to test the study hypotheses. Of these, 54 responses were returned, representing a 90% response rate. The SPSS statistical system was used for data analysis, and the t-test method was applied to test the hypotheses. The findings revealed that external audit bodies play a significant role in enhancing the efficiency and effectiveness of the audit process. This is achieved through coordination between internal and external audit procedures, allowing for the detection of fundamental errors and distortions in financial statements when the audit process is properly planned. Additionally, the results showed that external auditors contribute to reducing financial corruption by increasing the credibility of the data in the financial statements. The study emphasizes that external audit processes are essential in identifying discrepancies in financial records, thereby ensuring greater transparency and accuracy in reporting. The study also suggests several recommendations, such as addressing the root causes of corruption, rather than simply launching campaigns. These measures are critical, particularly for individuals living in poverty and deprivation, who may be more susceptible to corrupt practices. The research highlights the need for a more comprehensive approach to combating financial corruption, which involves not only external oversight but also fostering a culture of integrity within organizations. Moreover, the study advocates for stronger collaboration between internal and external audit bodies to enhance the overall effectiveness of corruption prevention mechanisms. This research contributes to the understanding of how external oversight can serve as a crucial tool in mitigating financial corruption and improving the integrity of financial reporting.